2015
DOI: 10.1111/jpy.12330
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity and biogeographic variation in physiology of habitat‐forming seaweed: response to temperature and nitrate

Abstract: Southeastern Australian waters are warming at nearly four times the global average rate (~0.7°C · century(-1) ) driven by strengthening incursions of the warm oligotrophic East Australian Current. The growth rate hypothesis (GRH) predicts that nutrient depletion will impact more severely on seaweeds at high latitudes with compressed growth seasons. This study investigates the effects of temperature and nutrients on the ecophysiology of the habitat-forming seaweed Phyllospora comosa in a laboratory experiment u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 59 publications
(120 reference statements)
6
38
1
1
Order By: Relevance
“…() and Flukes et al. () found no effects of nitrate but strong negative effects of current summer temperatures (22°C) on growth and survival of E. radiata and P. comosa , concluding that long‐term warming would have severe population‐level effects. Consequently, although physiological data are only available for very few of the modelled species, it appears they currently fill their thermal niches, at least within their biogeographic provinces (cf.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…() and Flukes et al. () found no effects of nitrate but strong negative effects of current summer temperatures (22°C) on growth and survival of E. radiata and P. comosa , concluding that long‐term warming would have severe population‐level effects. Consequently, although physiological data are only available for very few of the modelled species, it appears they currently fill their thermal niches, at least within their biogeographic provinces (cf.…”
Section: Discussionmentioning
confidence: 98%
“…These results also align with experimental data demonstrating that temperature is the dominant factor limiting the performance and survival of Phyllospora comosa, Scytothalia dorycarpa, Sargassum spp. and Ecklonia radiata compared to non-climatic factors (Flukes, Wright, & Johnson, 2015;Mabin et al, 2013;Provost et al, 2017;Xiao et al, 2015). For example, Mabin et al (2013) Total length of temperate coastline was estimated to be 26,730 km.…”
Section: Discussionmentioning
confidence: 99%
“…The photosystem of juvenile brown algae possess rapid phenotypic buffering (plasticity; Flukes et al. ; C. Mabin, unpub. data) which suggests that environmental factors influence F v / F m .…”
Section: Discussionmentioning
confidence: 99%
“…Phyllospora photosynthetic efficiency, growth, and survival appear to be negatively correlated with higher summer temperatures (22°C; Flukes, Wright, & Johnson, ) and in NSW, plants have higher δ 13 C, photosynthetic capacity (rETRmax), and concentrations of chl c and fucoxanthin compared to Tasmania. However, as with morphology (Peters, ), these traits appear to be highly plastic and rapidly converge under similar environmental conditions (Flukes et al., ). Supporting this finding, Weigner () found no latitudinal pattern in Phyllospora tissue chemistry along a 5 degree latitudinal gradient in NSW.…”
Section: Biology Of Australia's Subtidal Fucoid Forestsmentioning
confidence: 99%
“…It has been experimentally demonstrated that Scytothalia can acclimate in response to UVB and increased its light absorption efficiency in the UV bands by upregulating synthesis of photoprotective compounds (Xiao et al., ). Similarly, Phyllospora physiology is also highly plastic and rapidly responds to change in abiotic conditions (Flukes et al., ). Certainly, thresholds exist beyond which these species will be unable to compensate, and these thresholds are likely to be determined by a range of factors including dispersal capacity and population connectivity mediating genetic diversity and capacity to adapt (Wernberg et al., in review).…”
Section: Threats and Declines Of Australia's Fucoid Forestsmentioning
confidence: 99%